2015
DOI: 10.30843/nzpp.2015.68.5791
|View full text |Cite
|
Sign up to set email alerts
|

Forest efficacy trials on phosphite for control of kauri dieback

Abstract: In 2012, trials were established in four kauri forest sites severely affected by kauri dieback (Phytophthora agathidicida = P. taxon Agathis, PTA) to determine the potential of phosphorous acid (phosphite) as a control tool. Baseline assessments of 162 trial trees included canopy disease rating, trunk lesion dimensions and lesion activity (recent bleeding/ oozing). Phosphite (Agrifos®600) at concentrations of 7.5% or 20% was injected (20 ml) at 20-cm intervals around the trunk. Control trees were left untreate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 7 publications
0
26
0
Order By: Relevance
“…As this species is an emerging pathogen that was only formally described in 2015 ( Weir et al, 2015 ), comparatively little research has been carried out on treatment options. To date, phosphorous acid (phosphite) is the only chemical that has been used on kauri trees affected by P. agathidicida , and while this has proved an effective treatment, some signs of phytotoxicity were present at higher treatment concentrations ( Horner and Hough, 2013 ; Horner et al, 2015 ). The EC 50 for mycelial growth inhibition by phosphite was 4 μg/ml ( Horner and Hough, 2013 ), similar to the EC 50 we measured for benzethonium chloride (3.2 μg/ml).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As this species is an emerging pathogen that was only formally described in 2015 ( Weir et al, 2015 ), comparatively little research has been carried out on treatment options. To date, phosphorous acid (phosphite) is the only chemical that has been used on kauri trees affected by P. agathidicida , and while this has proved an effective treatment, some signs of phytotoxicity were present at higher treatment concentrations ( Horner and Hough, 2013 ; Horner et al, 2015 ). The EC 50 for mycelial growth inhibition by phosphite was 4 μg/ml ( Horner and Hough, 2013 ), similar to the EC 50 we measured for benzethonium chloride (3.2 μg/ml).…”
Section: Discussionmentioning
confidence: 99%
“…Kauri dieback was first recognized over 40 years ago ( Gadgil, 1974 ) and is continuing to spread through the forests of northern New Zealand, rapidly killing trees of all ages and sizes ( Beever et al, 2009 ). Currently, there are no established treatment or control options for P. agathidicida , although the use of phosphite as a potential treatment for infected trees is being explored ( Horner and Hough, 2013 ; Horner et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Trials on diseased kauri trees showed dramatic healing of P. agathidicida ‐induced lesions following trunk injection with 7.5–20% phosphite (Horner & Hough, ; Horner et al , ), whereas lesions on untreated trees continued growing (Fig. e,f).…”
Section: Current Disease Management Strategiesmentioning
confidence: 99%
“…Secondly, in comparison with vegetation removal or thinning, chemical protection of tanoak with Agri-fos ® incurs considerably greater economic costs [43] and social and legal constraints to its implementation [38] (Q2c,d). While this and similar chemicals can be efficacious in preventing infection or disease from a range of Phytophthora [54], much remains unclear about their mode of action, interaction with the host genotype, and overall efficacy. A cost-effective coverage of chemical protection within stands is likely to be restricted by individual variation in treatment efficacy and variation in treatment costs.…”
Section: Management Strategies-effects On Disease Impacts (Q2ad)mentioning
confidence: 99%
“…These expectations are testable against field experiments and highlight influential parameter uncertainties, and, therefore, offer insights that could inform future research and practice of tree disease management and conservation. Our results are aimed at informing the management of P. ramorum in the Western USA, but could be leveraged to inform affected or at-risk areas in Western Europe and Eastern USA, and chemical protection strategies for other emerging Phytophthora worldwide [19,24,40,54]. Of course, an extension of this modelling effort, or similar de novo efforts require a careful examination of assumptions, and likely changes to those dictating dispersal, efficacy, and species-level infection and mortality dynamics.…”
Section: Experimental Testing and Extension To Other Systemsmentioning
confidence: 99%